Analisis Pengaruh Earning Per Share, Valuasi Harga Saham, dan Leverage terhadap Nilai Perusahaan pada Perusahaan Sektor Transportasi dan Logistik yang Tercatat di Bursa Efek Indonesia Periode 2015-2019 - Kumba Digdowiseiso; Bambang Susilo; Lily Sri Utami (Syntax Literate, 2022)
This study aims to determine the effect of variables from Earning Per Share (EPS), Stock Price Valuation as measured by Price Earning Ratio (PER), and Leverage variables as measured by Debt to Ratio (DER) on Company Value in Transportation and Logistics sector companies that listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study includes 40 Transportation and Logistics sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique used purposive sampling and obtained a sample of 16 companies. This study uses secondary data in the form of financial statements that have met the criteria, data obtained from financial statements that can be accessed via www.idx.co.id. The analytical technique used in this study is linear regression of panel data using the STATA 16 program. The results show that EPS and PER have a positive but not significant effect, while DER has a positive and significant effect on firm value.